Emprendimientos mapuchizados: una aproximación a la apropiación cultural de identidades mapuche en redes sociales - Maliqueo Orellana, Victoria (2022)
This paper is intended to offer the digital ethnographic research findings whereby I conduct a review and systematization of the emergence of various business on Instagram after the Chilean Protest (2019), noting the use of Mapuche repertorios as commercial identity, outstandingly in comparison with other decades. The question I proposed to answer was: What are the expressions of cultural appropriation of the Mapuche identity of Instagram business not belonging to this People, in the post Chilean protest period in Chile?, with the aim of: identify types of publications where these expressions of cultural appropriation are manifested, categorize them and understand the nature of their narratives; establish comparisons and analyze profiles according to the publications. To do this, I worked with a digital ethnographic method; reviewing this social network and selecting business publications, conducting in-depth interviews remotely with Mapuche entrepreneurs and conducting a mixed virtual Focus Group made up of different people, Mapuche and non-Mapuche consumers, diversity that allowed me to access different points of view on the subject. Meanwhile, in the theoretical proposal, I highlight the review of authors regarding to cultural appropriation and etnicity, as approaches that I expose with the aim of establishing a vision that makes this scenario more complex, where, the limits between valuing another culture, such as the Mapuche, and business techniques, are diffuse.